Our daily bread: communication as a mission and ministry of the church - Achtelstetter, Karin (Documentation, 2010)
Today the role of communication in relation to the churches’ selfunderstanding and programs is shifting. The communication pendulum swings from communication as a mission and ministry of the church to communication as a public information service for the churches. In 2009 the LWF organized an international consultation on “Communication: Our Daily Bread. Communication as a Mission and Ministry of the Church” at the Theological Faculty of the Friedrich- Alexander University in Erlangen, Germany. The meeting provided a platform where church communicators, policy makers, mission societies and other agencies could exchange information, discern new trends and discuss their expectations for communication in the churches in the 21st century. Here are their expectations. (Verlagsinformation)